Relações trabalhistas e estilo de vida do atleta profissional de futebol do Rio Grande do Norte - Miranda, Hênio Ferreira de (2005)
Brazilian Law n° 9.615 of 24 March, 1998 established new paradigms in the employment relations existent between the soccer athlete and the sport association, both of whom are accustomed to the former legislation. They do not seem to have organized themselves in the sense of understanding the practical effects of the legal precepts currently in force, raising doubts that hinder the professional practice of the former and the performance of the latter in relation to managing these human resources. The purpose of this study is to analyze the degree of knowledge displayed by the professional soccer athlete about the legal recourses at his disposal in relation to the employment relations established in his work contract, as well as investigating the stress habits and stress situations that he most often experiences. This descriptive study consisted of a sample of 105 players under contract with clubs participating in the final phase of the state soccer championship. A questionnaire was used as the data collection instrument, whose analysis allows us to verify the lack of knowledge, on the part of the subjects studied, about the laws that regulate their profession, as well as identifying the stress habits and stress situations that are most reflected in their lifestyle. The lack of knowedge of regulate norms of their profession influences, in a negative way, in the lifestyle of soccer professional athlete from Rio Grande do Norte, Brasil